Tell me three things - Buxbaum, Julie (New York Delacorte Press, 2016)
Sixteen-year old Jessie, still grieving over her mother's death, must move from Chicago to "The Valley," with a new stepfamily but no new friends until an anonymous fellow student emails and offers to help her navigate the school's treacherous social waters
1
Keywords: Dating (Social customs) -- Fiction; Grief -- Fiction; High schools -- Fiction; Moving, Household -- Fiction; Schools -- Fiction; Stepfamilies -- Fiction; Los Angeles (Calif.) -- Fiction